The relationship between time perspective and career maturity for grade 11 and 12 learners - Pieterse, Anna Margaretha (University of the Free State, 2005)
The main aim of this study was to investigate the occurrence of possible differences in the time perspective and career maturity for learners of different grades (Gr. 11 and Gr. 12), genders (male and female) and school environments (advantaged, transit and disadvantaged). The second aim was to establish whether the time perspective of learners c ould be used to indicate a significant percentage of variance in their career maturity. The findings indicated that differences do exist in time perspective and career maturity for learners of different grades, genders and school environments. It was found that learners from disadvantaged schools are most focused on the future, while learners in advantaged schools are least focused on the future. Also, male learners in advantaged schools are less focused on the future than any other group. Learners from advantaged schools achieved the highest average in career maturity , while learners from disadvantaged schools achieved the lowest. It was also found that time perspective can be used to predict a significant percentage of variance in the career maturity of Gr. 11 and 12 learners.
Dissertation (M.Soc.Sc. (Counselling Psychology))--University of the Free State, 2005
Keywords: Vocational education; Vocational guidance; Time perspective; Career development; Future time perspective; Present time perspective; Career maturity; Career guidance; Career decisions; Adolescents; Gender differences; Previously disadvantaged school environment; Previously advantaged school environment; Attitude; Transition from secondary to tertiary education